The influence of an electron beam on the frequency of appearance of modifications and mutagens in the residual florula - Antipov, V.S.; Babych, E.M.; Berezhna, I.V.; Hirna, T.V.; Kornilov, E.O.; Kiselev, V.A.; Linnik, A.F.; Sklar, N.I.; Uskov, V.V. (Вопросы атомной науки и техники, 2006)
We have carried out a series of tests for studying an electron beam (Е=4 МеV) influence on adaptive mutability
test cultures of the sanitary-model microflora in various regimes (0.4…3.2 kGy) of processing samples of natural
water and sewages. Mutafacient properties and modifications of the residual microflora stimulated by the electron
beam effect are scarcely pronounced. They do not indicate themselves in the regimes that guarantee the water purification
up to the indices stipulated by the corresponding standards. Проведен цикл экспериментов по влиянию электронного пучка (Е=4 МеV) на адаптивную изменчивость тест-культур санитарно-показательной микрофлоры в условиях разных режимов (0,4…3,2 кГр) обработки проб природных и сточных вод. Установлено, что мутагенные свойства и модификация остаточной микрофлоры после воздействия электронного пучка имеют слабо выраженный характер и не проявляются в режимах, которые обеспечивают очистку воды до санитарных норм. Проведено цикл експериментів по впливу електронного пучка (Е=4 МеВ) на адаптивну мінливість тест-
культур санітарно-показової мікрофлори в умовах різних режимів (0,4…3,2 кГр) обробки проб природних та
стічних вод. Встановлено, що мутагенні властивості та модифікація залишкової мікрофлори після впливу
електронного пучка мають слабко виражений характер і не проявляються в режимах, що забезпечують
очистку води до санітарних норм.